Biopsy-Proven Amyloid-Beta Related Angiitis with Unusual Presentation and Long-Term Follow-Up. (October 2022) - Gupta, Navnika; Galla, Krishna; Pichler, Michael R.; McComb, Rodney D.; Helvey, Jason T.; Fayad, Pierre
Amyloid-beta related angiitis (ABRA) is a rare central nervous system inflammatory and vasculitic process. It is seen in patients with cerebral amyloid angiopathy (CAA) and thought to be mediated by an autoimmune reaction against cerebrovascular β-amyloid. We describe the case of a patient with ABRA with clinical information and brain imaging over a 10-year period. The patient was hospitalized in 2018 for altered mental status, paranoia and hallucinations. Her symptoms started in 2009 with an episode of vertigo and loss of consciousness. From 2011-2019, she had multiple episodes of transient focal neurological deficits with overall cumulative progressive decline in cognition and functional status. Retrospective and comparative reviews of brain magnetic resonance imaging (MRI) from 2009-2019 showed waxing and waning vasogenic cerebral edema with overall progression of white matter hyperintensities and peripheral micro-hemorrhages consistent with inflammatory CAA. Re-examination of a brain biopsy from 2009 showed ABRA, and immunostaining was positive for β-amyloid. She was treated with intravenous steroids with minimal symptomatic improvement. She was lost to our follow-up after hospital discharge. We describe the temporal progression of ABRA through serial brain imaging over a 10-year period. To our knowledge, this is the longest published follow-up duration of ABRA. The patient in our case had severe cognitive impairment and disability despite treatment with steroids.